Are tolerance and training required to end TB?. Issue 11 (November 2018) - Divangahi, Maziar
Host defence strategies againstMycobacterium tuberculosis (Mtb), the bacterium that causes tuberculosis (TB), include host resistance and disease tolerance. To date, most studies have focused on resistance mechanisms, but developing new strategies to eradicate Mtb will require an understanding of the entire landscape of immunity in TB. Here I discuss two evolutionarily conserved host defence strategies, disease tolerance and trained immunity (memory-like innate immune responses), and their role in Mtb infection. In this comment, Maziar Divangahi discusses the roles of disease tolerance and trained immunity in tuberculosis infection.